Involvement of a PadR regulator PrhP on virulence of Ralstonia solanacearum by controlling detoxification of phenolic acids and type III secretion system. (8th August 2019) - Zhang, Yong; Zhang, Weiqi; Han, Liangliang; Li, Jing; Shi, Xiaojun; Hikichi, Yasufumi; Ohnishi, Kouhei
Summary: Ralstonia solanacearum can metabolize ferulic acid (FA) and salicylic acid (SA), two representative phenolic acids, to protect it from toxicity of phenolic acids. Here, we genetically demonstrated a novel phenolic acid decarboxylase regulator (PadR)‐like regulator PrhP as a positive regulator on detoxification of SA and FA in R. solanacearum . Although the ability to degrade SA and FA enhances the infection process of R. solanacearum toward host plants, PrhP greatly contributes to the infection process besides degradation of SA and FA. Our results from the growth assay, promoter activity assay, RNA‐seq and qRT‐PCR revealed that PrhP plays multiple roles in the virulence of R. solanacearum : (1) positively regulates expression of genes for degradation of SA and FA; (2) positively regulates expression of genes encoding type III secretion system (T3SS) and type III effectors both in vitro and in planta ; (3) positively regulates expression of many virulence‐related genes, such as the flagella, type IV pili and cell wall degradation enzymes; and (4) is important for the extensive proliferation in planta . The T3SS is one of the essential pathogenicity determinants in many pathogenic bacteria, and PrhP positively regulates its expression mediated with the key regulator HrpB but through some novel pathway to HrpB in R. solanacearum . This is the first report on PadR regulators to regulate the T3SS and it could improve our understanding of the various biological functions of PadR regulators and the complex regulatory pathway on T3SS in R. solanacearum .